SYNTHESIS POLYMER FOR ENHANCED OIL RECOVERY APPLICATION - RANI (NIM : 20511010); Pembimbing : Prof. Dr. Ing Cynthia Linaya Radiman, DEA, ENENG
Polymer can be applied in Enhanced Oil Recovery to improve oil productivity. In petroleum industry, it was added to injection brine to increase the viscosity of fluids. In Indonesia at present, the polymer injection is still not implemented yet because the price of polymer material is still expensive. This work aims to synthesize polymer for EOR applications. The synthesis of Polymer A has been carried out by radical mechanism using X as initiator. The effects of monomer and initiator concentrations and reaction temperature on the molecular mass of the resulting polymers were studied. The optimum conditions for the synthesis of polymer A was monomer and initiator concentration of 1.4086 mol/L and 2.1711 x 10-3 mol/L, respectively, and reaction temperature of 60 oC. This condition was then used for the synthesis of polymer B by modification of polymer A. The Intrinsic viscosity and vicosity-average molecular mass of polymer A and polymer B were determined by viscometry method. The optimum viscosity-average molecular mass of polymer A was 2.709 x 106 g/mol, while the intrinsic viscosity of polymer B was 15.9115 dL/g. Based on the measurement of rheological properties of polymers, it can be concluded that the dynamic viscosity of polymer increases with the increasing the polymer concentration. To achieve the same viscosityÃ‚Â’s value, polymer B and HYBOMax needs smaller concentration than polymer A. Polymer B has better thermal stability and also has good resistance to shear rate than polymer A and HYBOMax. On the other hand, polymer A and polymer B have a better resistance towards salt concentration than HYBOMax.